Endodontic Cryotherapy: A Review - Dr. Apeksha Ghatge; Dr. Asha Jha; Dr. Sanija Sundaresan; Dr. Radhika Yagnik Gupta; Dr. Sejal Gupta; Dr. H. L Gupta (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Endodontic cryotherapy involves using cold therapy during root canal treatments to reduce inflammation, pain, and improve patient comfort. This review examines the efficacy, mechanisms, and clinical outcomes of cryotherapy in endodontics. Preliminary findings suggest it enhances analgesic effects post-treatment, warranting further research for standardized protocols and long-term benefits.